2009
DOI: 10.1007/bf03218924
|View full text |Cite
|
Sign up to set email alerts
|

Study on the optimization of cationic ring opening polymerization of silicone-based epoxy monomers for holographic photopolymers

Abstract: This study examined the optimum compositions of binder, photo-acid generator (PAG) and sensitizer for the cationic ring opening polymerization of 1,3-bis[2-(3-{7-oxabicyclo-[4.1.0]heptyl})]-tetramethyldisiloxane in the presence of polydimethylsiloxane with four epoxide moieties as a co-monomer. When diffractive efficiency (DE) values were compared quantitatively to analyze the effect of the binder on holographic photopolymerization, DE was affected by the viscosity of the binders and miscibility with the monom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In 2009, Kim and Chung [73] optimised a photopolymer system made from complex compositions of binder, photoacid generator (PAG), and sensitiser involving the cationic ring-opening polymerization of 1,3-bis[2-(3-7-oxabicyclo-[4.1.0]heptyl)]-tetramethyldisiloxane in the presence of polydimethylsiloxane, with four epoxide moieties as a comonomer. It was found that when diffractive efficiency values were compared quantitatively, in order to analyse the effect of the binder on holographic photopolymerisation, the diffractive efficiency was affected by the viscosity of the mixture.…”
Section: Physics Research Internationalmentioning
confidence: 99%
“…In 2009, Kim and Chung [73] optimised a photopolymer system made from complex compositions of binder, photoacid generator (PAG), and sensitiser involving the cationic ring-opening polymerization of 1,3-bis[2-(3-7-oxabicyclo-[4.1.0]heptyl)]-tetramethyldisiloxane in the presence of polydimethylsiloxane, with four epoxide moieties as a comonomer. It was found that when diffractive efficiency values were compared quantitatively, in order to analyse the effect of the binder on holographic photopolymerisation, the diffractive efficiency was affected by the viscosity of the mixture.…”
Section: Physics Research Internationalmentioning
confidence: 99%